ANALISIS PERLAKUAN AKUNTANSI PADA PENGELOLAAN MATERIAL LIMBAH NON B3 DI GUDANG LOGISTIK PT.PLN (PERSERO) UP3 PEMATANGSIANTAR - Khansa Zahirah Nasution; Kamilah K (JURNAL AKUNTANSI, 2023)
This research aims to explain how the management of non-B3 waste materials and their accounting treatment for the management of unused materials so that the recording and accounting disclosures of waste can be presented in the financial statements. This Research uses descriptive qualitative method. Data analysis techniques used in data collection are interviews and observations. The results of this study are non-B3 waste management and accounting treatment at PT. PLN (Persero) UP3 Pematangsiantar has done well. non B3 waste material is recognized as an expense because it uses the operating budget in its use. Another reason is that non-B3 waste material cannot be recognized as an asset because it comes from material that uses an operating budget which requires maintenance costs so that it is recognized as an expense. The mechanism for managing non-B3 waste materials will eventually become a source of other income.